Ozone Solubility in Aqueous Solutions of NaCl, Na2SO4, and K2SO4: Application of the Weisenberger-Schumpe Model for Description of Regularities and Calculation of the Ozone Molar Absorption Coefficient. (4th March 2017) - Ershov, Boris G.; Gordeev, Andrey V.; Seliverstov, Aleksandr F.
ABSTRACT: The ozone solubility in aqueous solutions of salts, NaCl (up to 5 М) and Na2 SO4 (up to 2 М) and their mixtures, was studied. The results are adequately described by the semi-empirical model proposed by Weisenberger and Schumpe for calculation of the solubilities of atmospheric gases in concentrated solutions of electrolytes. By comparing the data obtained experimentally and calculated in terms of the Weisenberger and Schumpe model, the ozone molar absorption coefficient was found to be ε  = 2860 ± 200 M −1 cm −1 at 260 nm.